Experimental study on tribological property of mechanical seals with changeable pore diameter - Ma Chenbo; Duan Yan Jun; Sun Jianjun (Functional Materials, 2016)
To study tribological property of mechanical seals when distributing micropores along the radial face with changeable parameter, friction experiments of mechanical seals under a certain condition were carried out while the pore diameter changed. The results show that: the introduction of micropores on the surface can reduce the friction efficiently, but its antifriction effect is closely related to the distribution of micropores. The friction coefficient is the smallest when pore diameters increasing by degrees along the seal radial face from the inside out, while complexly distributed of pore diameter has a poor effect on antifriction of mechanical seals. The results can offer some help for optimal design of mechanical seals with micropores.